Identifikasi Strategi Kesiapsiagaan Bencana Dalam Kelompok Masyarakat (Studi Kasus Desa Kungkai Baru Kecamatan Air Periukan Kabupaten Seluma) - Diyas Widiyarti; Heni Nopianti (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2021)
Every province in Indonesia can be categorized as a vulnerable area due to its strategic location on the connectivity of the potential of natural resources. The object of study in this study is a rural area in Seluma district named Kungkai Baru village. Readiness studies at lower levels such as local institutions (kelurahan/desa) have not been found, even though the kelurahan/village is a local level institution that has direct contact with the community. This study uses a descriptive quantitative approach, using primary data collection survey questionnaires by looking at the relationship between the independent and dependent variables that have been determined previously. The results of the study showed that preparedness was stated in 1). The attitude of the individual (family) is good. 2). The level of knowledge obtained based on literacy is still low. 3). Mobilization of resources to minimize disaster risk stemming from the experience of each individual becomes a strategy that is carried out independently with an alternative to the evacuation route, namely to the hilly area which is on the west route of Kungkai Baru village to take shelter and save themselves during a disaster. 4). The organization of the new kungkai village community group together in carrying out reforestation activities, currently in 2016 as a conservation area and tourist attraction named "cemoro sewu" or (a thousand fir).